2000
DOI: 10.1038/sj.cdd.4400597
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 inhibits Bax translocation from cytosol to mitochondria during drug-induced apoptosis of human tumor cells

Abstract: The pro-apoptotic protein, Bax, has been reported to translocate from cytosol to mitochondria following exposure of cells to apoptotic stresses including cytokine withdrawal and treatment with glucocorticoids and cytotoxic drugs. These observations, coupled with reports showing that Bax causes the release of mitochondrial cytochrome c, implicate Bax as a central mediator of the apoptotic process. In this report we demonstrate by subcellular fractionation a significant shift in Bax localization from cytosol to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
233
2
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(256 citation statements)
references
References 38 publications
14
233
2
2
Order By: Relevance
“…For example, in the nanodisc cryo-EM study, Volkmann et al 78 found that BCL-XL abolished the integration of BAX into nanodisc membranes in the presence of BID BH3 peptides. This agrees with other work 10,34,95,[110][111][112] showing that BCL-XL or BCL-2 can block membrane recruitment and integration of BAX, even in the presence of a BAX-activating signal. In other studies, membrane integration of both BCL-XL and BAX (i.e.…”
Section: How Does Bcl-xl Protect Against Cell Death?supporting
confidence: 92%
“…For example, in the nanodisc cryo-EM study, Volkmann et al 78 found that BCL-XL abolished the integration of BAX into nanodisc membranes in the presence of BID BH3 peptides. This agrees with other work 10,34,95,[110][111][112] showing that BCL-XL or BCL-2 can block membrane recruitment and integration of BAX, even in the presence of a BAX-activating signal. In other studies, membrane integration of both BCL-XL and BAX (i.e.…”
Section: How Does Bcl-xl Protect Against Cell Death?supporting
confidence: 92%
“…Moreover, ROS have also been implicated on the release of cytochrome c and other apoptosis-inducing factors, as well as on the upstream of caspases involved in the apoptotic cascade [10,[51][52][53]. Although it has been reported that in cytochrome c-induced cell death, cytochrome c release may occur by both MPT-dependent and independent mechanisms, several studies have shown that MPT and cytochrome c release are early events in several model of apoptosis [4,6,7,19,54]. Moreover, the pro-apoptotic protein Bax, implicated in the release of cytochrome c, has been suggested to translocate from the cytosol to mitochondria in cells under the action of VP-16, a process that is prevented by the anti-apoptotic protein Bcl-2 [53], which inhibits the MPT by keeping the pyridine nucleotides in a relative reduced state [42,55].…”
Section: Discussionmentioning
confidence: 99%
“…[84][85][86] Staurosporine, a potent apoptosis inducer demonstrated in a broad spectrum of cells activate apoptosis through the mitochondrial death pathway. [87][88][89][90][91] The proapoptotic members of the Bcl-2 family play a critical role in staurosporineinduced apoptosis. Cells lacking both Bax and Bak are known to be completely resistant to multiple apoptotic stimuli including staurosporine.…”
Section: Signaling Pathway Mediating Staurosporineinduced Apoptosismentioning
confidence: 99%
“…These downstream events induced by staurosporine in vector-transfected HLE cells are similar to those reported in other cell lines. [87][88][89][90][91] In either HaA-or HaB-transfected cells, the staurosporine-induced downstream events were largely turned off. Thus, our results provide additional evidence that both Bax and Bak are important for staurosporine-induced apoptosis.…”
Section: Signaling Pathway Mediating Staurosporineinduced Apoptosismentioning
confidence: 99%